Committing to Keep Clean: Nudging Complements Standard Policy Measures to Reduce Illegal Urban Garbage Disposal in a Neighborhood With High Levels of Social Cohesion - Merkelbach, Inge; Dewies, Malte; Denktas, Semiha (Frontiers in Psychology, 2021)
Illegal garbage disposals are a persistent urban problem, resulting in high clean-up costs, and nuisance and decreased satisfaction with the neighborhood among residents. We compared three adjacent city-areas in Rotterdam in which, for two weeks, either 1) no action to decrease illegal garbage disposals was taken, 2) standard door-to-door canvassing was carried out, or 3) door-to-door canvassing was enriched with several nudges, most importantly a commitment-nudge. The nudging condition proved highly effective, reducing illegal disposals at post-test and follow-up (two months later) with two-thirds, resulting in a very large effect size (d = 2.60). At post-test, standard door-to-door canvassing did not differ from the control condition, but at follow-up results were comparable to the nudging-condition. This could however be due to spill-over effects. Using a commitment nudge proved highly effective in decreasing illegal garbage disposals, however effects might be specific to neighborhoods with strong social cohesion.